1996
DOI: 10.1111/j.1751-1097.1996.tb01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low‐Dose UVA Irradiation Induces Local Suppression of Contact Hypersensitivity, Langerhans Cell Depletion and Suppressor Cell Activation in C3H/HeJ Mice

Abstract: It has previously been demonstrated that chronic low-dose solar-simulated UV radiation could induce both local and systemic immunosuppression as well as tolerance to a topically applied hapten. In this study, we have used a chronic low-dose UV-irradiation protocol to investigate the effects of UVA on the skin immune system of C3H/ HeJ mice. Irradiation with UVA + B significantly suppressed the local and systemic primary contact hypersensitivity (CHS) response to the hapten 2,4,6-trinitrochlorobenzene. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 27 publications
0
48
3
Order By: Relevance
“…In contrast, a recent study by Bestak and Halliday [5] has found that UVA irradiation, at a total dose of UVA equivalent to the dose we have used, but administered chronically in 20 exposures rather than as a single exposure, significantly suppressed the local, but not the systemic contact hypersensitivity reaction in haired mice. It is difficult to reconcile this opposite finding from our study, apart from noting the differences in mouse strain and irradiation regime.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In contrast, a recent study by Bestak and Halliday [5] has found that UVA irradiation, at a total dose of UVA equivalent to the dose we have used, but administered chronically in 20 exposures rather than as a single exposure, significantly suppressed the local, but not the systemic contact hypersensitivity reaction in haired mice. It is difficult to reconcile this opposite finding from our study, apart from noting the differences in mouse strain and irradiation regime.…”
Section: Discussioncontrasting
confidence: 44%
“…However the immunological consequences of ultraviolet A (UVA) radiation (320-400 nm) exposure are currently less well-defined and more controversial. Experimentation in mice has produced evidence that UVA radiation has an immunosuppressive action [5], or conversely has no effect on the immune status [1,6,7]. In addition, recent evidence indicates that UVA irradiation induces the photoisomerisation of trans-urocanic acid in mouse and human skin [8][9][10], but that this reaction is not necessarily followed by immune suppression [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, UVAI but not UVAII also caused significant, dose-responsive immunosuppression in vivo in humans. Chronic low-dose UVA, similarly to UVB, reduces Langerhans cells from the epidermis of mice and results in activation of tolerance as shown by transfer of suppressor cells [21]. UVAII was previously found to cause immunosuppression in mice and humans, via mechanisms which appear similar to those following UVB exposure [22,23].…”
Section: Discussionmentioning
confidence: 96%
“…35,36 Mechanistic studies using sunscreens and AOxs specifically implicate ROS in UV-induced immunosuppression, measured by depletion of epidermal Langerhans cells (LC) and suppression of contact hypersensitivity in skin studies. 37 With the application of sunscreen, depletion of epidermal LC is prevented and delayed hypersensitivity is improved. The degree of protection is directly related to the level of UVA protection.…”
Section: Immunosuppressionmentioning
confidence: 99%